2013
DOI: 10.1016/j.pain.2013.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Social stress exacerbates the aversion to painful experiences in rats exposed to chronic pain: The role of the locus coeruleus

Abstract: a b s t r a c tStressful experiences seem to negatively influence pain perception through as yet unknown mechanisms. As the noradrenergic locus coeruleus (LC) nucleus coordinates many components of the stress response, as well as nociceptive transmission, we evaluated whether the sensory and affective dimension of chronic neuropathic pain worsens in situations of stress due to adaptive changes of LC neurons. Accordingly, male rats were socially isolated for 5 weeks, and in the last 2 weeks, neuropathic pain wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 42 publications
2
27
0
1
Order By: Relevance
“…Concerning our failure to identify differences in mechanical sensitivity between CCI and OSS+CCI groups, it is interesting to note that Bardin et al (2009) as well as Bravo et al (2012, 2013) reported similar findings in a model of chronic mild stress and in a model of social isolation. Whereas the temperature of the cold plate test (5°C) used in the present study quite selectively stimulates cold nociceptors of the C-fiber type (Simone and Kajander, 1996), the von Frey filaments may activate a larger range of nociceptors belonging both to the C- and A-delta fiber categories (Martin et al, 1997).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Concerning our failure to identify differences in mechanical sensitivity between CCI and OSS+CCI groups, it is interesting to note that Bardin et al (2009) as well as Bravo et al (2012, 2013) reported similar findings in a model of chronic mild stress and in a model of social isolation. Whereas the temperature of the cold plate test (5°C) used in the present study quite selectively stimulates cold nociceptors of the C-fiber type (Simone and Kajander, 1996), the von Frey filaments may activate a larger range of nociceptors belonging both to the C- and A-delta fiber categories (Martin et al, 1997).…”
Section: Discussionmentioning
confidence: 58%
“…While some studies using psychological stressors observed an enhancement of pain sensitivity (Rivat et al, 2007; Burke et al, 2013), others failed to identify similar effects (Bravo et al, 2012, 2013). These divergent findings may partly be related to methodological differences with respect to the approaches chosen for stress induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the absolute number of TH-IR neurons increased in CMS animals, our electrophysiological data revealed a decrease in their activity, a finding that should be confirmed in further studies measuring noradrenaline levels in the LC and projection areas (frontal cortex and spinal cord) in basal and evoked conditions (after a painful or stressful event). Furthermore, we detected no changes in NAT or α2-adrenoceptor expression, indicating that the changes observed in spontaneous activity are probably caused by another neurotransmitter, possibly GABA (Bravo et al, 2013;Dimitrov et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
“…However, we observed increased avoidance of painful stimuli in animals subjected to CMS. Moreover, we subsequently demonstrated that in rats with neuropathic pain, social stress exacerbates aversion to painful experiences through a locus coeruleus (LC)-related mechanism (Bravo et al, 2013). Moreover, LC impairment coincides with the onset of anxio-depressive-like symptoms in rats suffering chronic neuropathic pain .…”
Section: Introductionmentioning
confidence: 90%